Corundum high-strength wear-resistant pouring material

By using sintered corundum aggregate and a variety of auxiliary materials, bonding agents and additives in corundum high-strength wear-resistant casting materials, the problem of insufficient refractory performance of the material in extremely high temperature environments and weaker ability to quench cold and heat, achieving higher refractory and thermal shock resistance, and extending service life.

CN119707460AInactive Publication Date: 2025-03-28JIANGSU SHUNXING REFRACTORY TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411957281.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing corundum high-strength wear-resistant casting materials have limited fire resistance in extreme high temperature environments and have weak ability to quench cold and heat, which may lead to cracking or peeling of the material, reducing the use effect and life.

Method used

Based on sintered corundum aggregate, combined with corundum fine powder, mullite fine powder, inorganic non-metallic materials and stainless steel fibers, calcium alumina cement, hydrated alumina, silica sol, aluminum dihydrogen phosphate and refractory clay, additives such as sintered spinel fine powder, silica fine powder, activated alumina fine powder and zirconium oxide fine powder are added to adjust the fluidity and plasticity of the casting material through a specific stirring process.

Benefits of technology

It significantly improves the refractory and thermal shock resistance of the casting material, prevents the material from cracking or peeling in high temperature environments, extends the service life of the product, and enhances its stability under extreme temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707460A_ABST
    Figure CN119707460A_ABST
Patent Text Reader

Abstract

The invention discloses a corundum high-strength wear-resistant castable, which belongs to the field of castable, and comprises a raw material, an auxiliary material, a binding agent and an additive, the raw material is corundum aggregate, and the auxiliary material comprises corundum fine powder, mullite fine powder, an inorganic non-metallic material and stainless steel fiber, the binding agent comprises calcium aluminate cement, hydrated alumina, silica sol, aluminum dihydrogen phosphate and refractory clay, and the additives comprise sintered spinel fine powder, silica micropowder, activated alumina micropowder, zirconia micropowder, a coagulant, a retarder, a dispersant, a flocculant, a plasticizer, a water-retaining agent, an anti-settling agent and a preservative. The corundum high-strength wear-resistant castable is prepared by mixing the raw materials, the auxiliary materials, the binding agent and the additive, so that the corundum high-strength wear-resistant castable has excellent strength, wear resistance, fire resistance and thermal shock resistance during use, and further the actual use effect and performance of the corundum high-strength wear-resistant castable are ensured; and the service life of the product is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of casting materials, in particular to a corundum high-strength and wear-resistant casting material. Background Art

[0002] High-strength wear-resistant castable is a cement-based composite single-component dry mortar, which is made of high-strength cement, mineral admixtures, high-strength aggregates and anti-cracking and wear-resistant agents through industrial production. High-strength wear-resistant castable can be used by adding water and mixing on site. It has good construction suitability. A certain thickness of anti-wear layer is formed on the surface of the silo or ore trough by artificial plastering. After normal maintenance, it can meet the technical requirements. It has high wear resistance, high bonding strength with the foundation concrete (steel silo), strong impact resistance, high compressive strength, good durability, and long service life. High-strength wear-resistant castable is specially used for the anti-wear layer of the lining of the slag ditch, ore trough, coal unloading trough, hopper, silo in the metallurgy, coal, thermal power, chemical, cement and other industries, and the anti-wear layer of the flood discharge gate and unloading hopper of water conservancy and hydropower, port and wharf projects, which plays a role in protecting the foundation concrete (or steel silo).

[0003] In the prior art, corundum high-strength wear-resistant casting material is a high-performance wear-resistant material, which is widely used in various industrial occasions that need to withstand wear, impact and high temperature. Although corundum casting material has high refractoriness, its refractoriness is still limited. In certain extreme high temperature environments, its refractoriness may be affected, resulting in a shortened service life. At the same time, due to its chemical composition, the ability of corundum wear-resistant casting material to resist rapid cooling and heating is relatively weak. In the case of rapid temperature changes, stress may occur, causing the material to crack or peel off, which not only reduces the use effect of corundum high-strength wear-resistant casting material, but also makes the refractoriness and thermal shock resistance of corundum high-strength wear-resistant casting material in high temperature environment poor, and shortens the service life of the product. Summary of the invention

[0004] The main purpose of the present invention is to provide a corundum high-strength wear-resistant casting material, which can effectively solve the problems in the background technology.

[0005] To achieve the above object, the technical solution adopted by the present invention is: A corundum high-strength wear-resistant castable, the formula materials for preparing the corundum high-strength wear-resistant castable include: raw materials, auxiliary materials, binders and additives, the raw materials are corundum aggregate, and the auxiliary materials include corundum fine powder, mullite fine powder, inorganic non-metallic materials and stainless steel fiber, the binder includes calcium aluminate cement, hydrated alumina, silica sol, aluminum dihydrogen phosphate and refractory clay, and the additives include sintered spinel fine powder, silicon dioxide fine powder, activated alumina fine powder, zirconium oxide fine powder, coagulant, retarder, dispersant, flocculant, plasticizer, water retaining agent, anti-settling agent and preservative.

[0006] Preferably, the corundum aggregate is one of sintered corundum, fused corundum, fused white corundum, fused brown corundum and zirconium corundum, and the mass percentage of the corundum aggregate is 60% to 80%.

[0007] Preferably, the corundum fine powder is one of white corundum fine powder, fused corundum fine powder, activated alumina fine powder and high-purity corundum fine powder, and the mass percentage of the corundum fine powder is 5% to 15%, the mass percentage of the mullite fine powder is 5% to 10%, the inorganic non-metallic material is one of quartz glass, alumina ceramics and zircon ceramics, and the mass percentage of the inorganic non-metallic material is 3% to 5%, and the mass percentage of the stainless steel fiber is 1% to 3%.

[0008] Preferably, the mass percentage of the calcium aluminate cement is 1% to 3%, the mass percentage of the hydrated alumina is 2% to 7%, the mass percentage of the silica sol is 3% to 5%, the mass percentage of the aluminum dihydrogen phosphate is 2% to 6%, the mass percentage of the refractory clay is 1% to 4%, and the refractory clay is one of high-alumina refractory clay, hard refractory clay, semi-hard refractory clay and soft refractory clay.

[0009] Preferably, the mass percentage of the sintered spinel fine powder is 1.2% to 1.4%, the mass percentage of the silica powder is 1.3% to 1.5%, the mass percentage of the activated alumina powder is 1.1% to 1.2%, the mass percentage of the zirconium oxide powder is 1.5% to 1.8%, the mass percentage of the coagulant is 0.2% to 0.3%, the mass percentage of the retarder is 0.3% to 0.4%, the mass percentage of the dispersant is 0.5% to 0.7%, the mass percentage of the flocculant is 0.1% to 0.3%, the mass percentage of the plasticizer is 0.6% to 0.8%, the mass percentage of the water retaining agent is 0.2% to 0.5%, the mass percentage of the anti-settling agent is 0.1% to 0.6%, and the mass percentage of the preservative is 0.4% to 0.8%.

[0010] Preferably, the mass percentage of the raw materials, auxiliary materials, binders and additives is 65%:20%:10%:5%.

[0011] A method for preparing a corundum high-strength wear-resistant casting material comprises the following steps: Step 1: Raw material preparation: Select and weigh high-quality raw materials, auxiliary materials, binders and additives according to mass percentage; Step 2: Crushing and screening: The raw materials are crushed and screened by integrated crushing and screening equipment to ensure uniform particle size distribution of the raw materials; Step 3, mixing preparation: put the raw materials weighed according to the mass percentage into a stirring device for mixing and stirring, and add the auxiliary materials, binders and additives weighed according to the mass percentage and an appropriate amount of water into the stirring device in sequence during the stirring process. At the same time, control the stirring time and stirring speed of the stirring device to adjust the fluidity and plasticity of the casting material, and obtain a corundum high-strength and wear-resistant casting material.

[0012] Preferably, the stirring time of the stirring device is set between fifteen minutes and twenty minutes, and the stirring speed of the stirring device is set between three thousand revolutions per minute and five thousand revolutions per minute.

[0013] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, corundum aggregate is used as the main load-bearing and refractory component. The corundum aggregate has the characteristics of high hardness, high wear resistance and high refractoriness, and is the basis for forming high-strength wear-resistant casting material. The corundum fine powder and mullite fine powder in the auxiliary material can fill the gaps between the aggregates to improve the density and strength of the casting material. At the same time, the mullite fine powder also has good thermal stability and thermal shock resistance, which helps to improve the overall performance. The addition of inorganic non-metallic materials and stainless steel fibers in the auxiliary material can enhance the tensile strength and crack resistance of the casting material. The stainless steel fiber can form an orderly reinforcement network in the casting material through the magnetic induction directional arrangement technology, providing additional stability and durability. The calcium aluminate cement and hydrated alumina in the binder can react chemically with the fine powder and additives in the auxiliary material to form a dense combined structure, improve the refractoriness and strength of the casting material, and then cooperate with silica sol, aluminum dihydrogen phosphate and refractory clay, which can further enhance the bonding force and high temperature resistance of the casting material, ensuring that a stable structure can be maintained under high temperature environment. The sintered spinel fine powder in the additive can optimize the thermal expansion coefficient and microstructure of the castable, thereby improving its thermal shock resistance. At the same time, spinel can also form a direct bond with other components in the matrix to improve the overall strength, and micropowders such as silica powder, activated alumina powder and zirconia powder can fill the tiny gaps in the castable to improve its density and wear resistance. In addition, they can also react chemically with the binder to generate highly heat-resistant compounds to further improve the fire resistance. Accelerators and retarders can control the setting time of the castable to ensure its stability and operability during the construction process. Dispersants and flocculants can improve the rheological properties of the castable, making it easier to construct and shape. At the same time, dispersants can prevent agglomeration and sedimentation between particles and improve the uniformity of the castable. Plasticizers and water-retaining agents can enhance the plasticity and water retention of the castable, so that it maintains a stable shape and performance during the construction process. Anti-settling agents and preservatives can prevent the castable from stratification and precipitation during storage, ensuring that it maintains stable performance for a long time, thereby achieving the purpose of improving the fire resistance and thermal shock resistance of the corundum high-strength wear-resistant castable during use, preventing the problem of material cracking or peeling, thereby ensuring the actual use effect and performance of the corundum high-strength wear-resistant castable and extending the service life of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The present invention is a schematic diagram of the preparation process of a corundum high-strength wear-resistant casting material. DETAILED DESCRIPTION

[0015] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application. Example

[0016] A corundum high-strength wear-resistant casting material, including formula materials for preparing the corundum high-strength wear-resistant casting material including: raw materials, auxiliary materials, binders and additives; raw material: The corundum aggregate is one of sintered corundum, fused corundum, fused white corundum, fused brown corundum and zirconium corundum, and the mass percentage of the corundum aggregate is 60% to 80%.

[0017] Excipients: The corundum fine powder is one of white corundum fine powder, fused corundum fine powder, activated alumina fine powder and high-purity corundum fine powder, and the mass percentage of the corundum fine powder is 5% to 15%; The mass percentage of mullite fine powder is 5% to 10%; The inorganic non-metallic material is one of quartz glass, alumina ceramics and zircon ceramics, and the mass percentage of the inorganic non-metallic material is 3% to 5%; The mass percentage of stainless steel fiber is 1% to 3%.

[0018] Binder: The mass percentage of calcium aluminate cement is 1% to 3%; The mass percentage of hydrated alumina is 2% to 7%; The mass percentage of silica sol is 3% to 5%; The mass percentage of aluminum dihydrogen phosphate is 2% to 6%; The mass percentage of the refractory clay is 1% to 4%, and the refractory clay is one of high-alumina refractory clay, hard refractory clay, semi-hard refractory clay and soft refractory clay.

[0019] additive: The mass percentage of sintered spinel fine powder is 1.2% to 1.4% The mass percentage of silica powder is 1.3% to 1.5%; The mass percentage of activated alumina powder is 1.1% to 1.2%; The mass percentage of zirconium oxide powder is 1.5% to 1.8%; The mass percentage of the coagulant is 0.2% to 0.3%; The mass percentage of retarder is 0.3% to 0.4%; The mass percentage of dispersant is 0.5% to 0.7%; The mass percentage of flocculant is 0.1% to 0.3%; The mass percentage of plasticizer is 0.6% to 0.8%; The mass percentage of water retaining agent is 0.2% to 0.5%; The mass percentage of the anti-settling agent is 0.1% to 0.6%; The mass percentage of the preservative is 0.4% to 0.8%.

[0020] The mass percentage between raw materials, auxiliary materials, binders and additives is 65%:20%:10%:5%. Example

[0021] like Figure 1 As shown, the specific steps of a method for preparing a corundum high-strength wear-resistant casting material are as follows: According to the mass percentage of raw materials, auxiliary materials, binders and additives and the mass percentage of each component of raw materials, auxiliary materials, binders and additives in the first embodiment, high-quality raw materials, auxiliary materials, binders and additives are selected and weighed, and then sintered corundum is selected as corundum aggregate and put into the integrated crushing and screening equipment to crush and screen the raw materials to ensure that the particle size distribution of the raw materials is uniform. Finally, the qualified sintered corundum aggregate after crushing and screening is put into the mixing equipment for mixing and stirring, and during the stirring process, the auxiliary materials composed of corundum fine powder, mullite fine powder, inorganic non-metallic materials and stainless steel fibers, calcium aluminate cement, hydrated alumina, silica sol, dihydrogen phosphate, etc., which are weighed according to the mass percentage, are added to the mixing equipment in sequence. A binder composed of aluminum and refractory clay and additives composed of sintered spinel fine powder, silica powder, activated alumina powder, zirconium oxide powder, accelerator, retarder, dispersant, flocculant, plasticizer, water retaining agent, anti-settling agent and preservative, and an appropriate amount of water, wherein the corundum fine powder is activated alumina fine powder, wherein the inorganic non-metallic material is alumina ceramic, and wherein the refractory clay is high-alumina refractory clay. At the same time, the stirring time and stirring speed of the stirring equipment are controlled, the stirring time of the stirring equipment is set between fifteen minutes and twenty minutes, and the stirring speed of the stirring equipment is set between three thousand and five thousand revolutions per minute, so as to adjust the fluidity and plasticity of the castable, and obtain a corundum high-strength and wear-resistant castable. Example

[0022] In implementation 2: Corundum aggregate: provides the main skeleton of the material, enhancing the strength and wear resistance of the material. Corundum has the characteristics of high strength, high hardness, high wear resistance and high chemical stability. It is an ideal aggregate for preparing high-strength wear-resistant castables. With corundum aggregate as the main load-bearing and refractory component, corundum aggregate has the characteristics of high hardness, high wear resistance and high refractoriness, which is the basis of high-strength wear-resistant castables.

[0023] Fine corundum powder: fills the gaps between aggregates, improves the density and strength of the material. At the same time, fine corundum powder can also increase the wear resistance and erosion resistance of the material; Mullite fine powder: provides excellent bonding performance and thermal stability, and enhances the overall performance of the material. Mullite has a lower creep rate and higher thermal shock stability, which helps to improve the high temperature resistance of the castable; Corundum fine powder and mullite fine powder, these fine powders can fill the gaps between aggregates and improve the density and strength of the castable. At the same time, mullite fine powder also has good thermal stability and thermal shock resistance, which helps to improve the overall performance.

[0024] Inorganic non-metallic materials: used to adjust the properties of castables or provide specific functions; Stainless steel fiber: Improves the toughness and thermal shock resistance of the material. Stainless steel fiber acts as a bridge in the material, resisting the crack propagation caused by thermal stress, thereby improving the overall strength and durability of the material; The addition of inorganic non-metallic materials and stainless steel fibers can enhance the tensile strength and crack resistance of the castable. Through magnetic induction directional arrangement technology, stainless steel fibers can form an orderly reinforcement network in the castable, providing additional stability and durability.

[0025] Calcium aluminate cement: forms a solid binding phase through hydration reaction, tightly combining the aggregate and powder in the material. Calcium aluminate cement has the characteristics of short setting time, high demoulding strength, and excellent high temperature performance. It is an important component for preparing refractory castables; Hydrated Alumina: Provides additional bonding strength and chemical stability; Calcium aluminate cement and hydrated alumina can chemically react with fine powder and additives in auxiliary materials to form a dense combined structure, thereby improving the refractoriness and strength of the castable.

[0026] Silica sol: helps to improve the thermal stability, fire resistance and physical strength of refractory materials; Aluminum dihydrogen phosphate: further provides additional binding strength and chemical stability; Refractory clay: provides bonding and plasticity, which helps in the shaping and processing of materials; Silica sol, aluminum dihydrogen phosphate and refractory clay can further enhance the bonding strength and high temperature resistance of the castable, ensuring that the structure remains stable in high temperature environments.

[0027] Sintered spinel fine powder: Improve the erosion resistance and wear resistance of the material. Sintered spinel has excellent chemical stability and high temperature performance, can resist the erosion of various corrosive media, can optimize the thermal expansion coefficient and microstructure of the castable, thereby improving its thermal shock resistance. At the same time, spinel can also form a direct bond with other components in the matrix to improve the overall strength; Silica powder: adjust the structure and properties of materials; Activated alumina powder: improves the activity and reactivity of the material and helps to form a strong binding phase with other ingredients; Zirconia powder: Improves the material's high temperature resistance and thermal shock resistance. Zirconia has an extremely high melting point and thermal stability, and is an important component for preparing high-temperature refractory materials; Silica powder, activated alumina powder and zirconia powder can fill the tiny gaps in the castable, improve its density and wear resistance. In addition, they can also chemically react with the binder to form high temperature resistant compounds, further improving the refractoriness.

[0028] Accelerator: accelerates the hydration reaction of cement and shortens the setting time of the material; Retarder: Delays the hydration reaction of cement, providing more operation time for construction; Accelerators and retarders can control the setting time of the castable and ensure its stability and operability during the construction process.

[0029] Dispersant: Improve the dispersibility and fluidity of materials, making aggregates and powders more evenly distributed in the material; Flocculant: used to adjust the suspension and sedimentation properties of materials, and helps with the shaping and processing of materials; Dispersants and flocculants can improve the rheological properties of castables, making them easier to construct and shape. At the same time, dispersants can prevent agglomeration and sedimentation between particles and improve the uniformity of castables.

[0030] Plasticizer: Improve the plasticity and processing properties of materials, making them easier to shape and process; Water-retaining agent: reduces the water loss of materials during preparation and construction, and maintains the wetness and plasticity of the materials; Plasticizers and water-retaining agents can enhance the plasticity and water retention of the castable, allowing it to maintain a stable shape and performance during the construction process.

[0031] Anti-settling agent: prevents stratification and settling of materials during storage and transportation; Preservative: prolong the storage time of materials and keep the performance of materials stable.

[0032] Anti-settling agents and preservatives prevent stratification and sedimentation of the castable during storage, ensuring that it maintains stable properties over a long period of time.

[0033] Therefore, the prepared corundum high-strength wear-resistant castable has excellent strength, wear resistance, fire resistance and thermal shock resistance.

[0034] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A corundum high-strength wear-resistant casting material, characterized in that: The formula materials for preparing corundum high-strength wear-resistant castables include: raw materials, auxiliary materials, binders and additives. The raw materials are corundum aggregates, and the auxiliary materials include corundum fine powder, mullite fine powder, inorganic non-metallic materials and stainless steel fibers. The binders include calcium aluminate cement, hydrated alumina, silica sol, aluminum dihydrogen phosphate and refractory clay. The additives include sintered spinel fine powder, silica powder, activated alumina powder, zirconium oxide powder, accelerators, retarders, dispersants, flocculants, plasticizers, water-retaining agents, anti-settling agents and preservatives.

2. The corundum high-strength wear-resistant casting material according to claim 1, characterized in that: The corundum aggregate is one of sintered corundum, fused corundum, fused white corundum, fused brown corundum and zirconium corundum, and the mass percentage of the corundum aggregate is 60% to 80%.

3. The high-strength and wear-resistant corundum casting material according to claim 2, characterized in that: The corundum fine powder is one of white corundum fine powder, fused corundum fine powder, activated alumina fine powder and high-purity corundum fine powder, and the mass percentage of the corundum fine powder is 5% to 15%, the mass percentage of the mullite fine powder is 5% to 10%, the inorganic non-metallic material is one of quartz glass, alumina ceramics and zircon ceramics, and the mass percentage of the inorganic non-metallic material is 3% to 5%, and the mass percentage of the stainless steel fiber is 1% to 3%.

4. The corundum high-strength wear-resistant casting material according to claim 3, characterized in that: The mass percentage of the calcium aluminate cement is 1% to 3%, the mass percentage of the hydrated alumina is 2% to 7%, the mass percentage of the silica sol is 3% to 5%, the mass percentage of the aluminum dihydrogen phosphate is 2% to 6%, the mass percentage of the refractory clay is 1% to 4%, and the refractory clay is one of high-alumina refractory clay, hard refractory clay, semi-hard refractory clay and soft refractory clay.

5. The high-strength and wear-resistant corundum casting material according to claim 4, characterized in that: The mass percentage of the sintered spinel fine powder is 1.2% to 1.4%, the mass percentage of the silica powder is 1.3% to 1.5%, the mass percentage of the activated alumina powder is 1.1% to 1.2%, the mass percentage of the zirconium oxide powder is 1.5% to 1.8%, the mass percentage of the coagulant is 0.2% to 0.3%, the mass percentage of the retarder is 0.3% to 0.4%, the mass percentage of the dispersant is 0.5% to 0.7%, the mass percentage of the flocculant is 0.1% to 0.3%, the mass percentage of the plasticizer is 0.6% to 0.8%, the mass percentage of the water retaining agent is 0.2% to 0.5%, the mass percentage of the anti-settling agent is 0.1% to 0.6%, and the mass percentage of the preservative is 0.4% to 0.8%.

6. The high-strength and wear-resistant corundum casting material according to claim 5, characterized in that: The mass percentage of the raw materials, auxiliary materials, binders and additives is 65%:20%:10%:5%.

7. The method for preparing a corundum high-strength wear-resistant casting material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Raw material preparation: Select and weigh high-quality raw materials, auxiliary materials, binders and additives according to mass percentage; Step 2: Crushing and screening: The raw materials are crushed and screened by integrated crushing and screening equipment to ensure uniform particle size distribution of the raw materials; Step 3, mixing preparation: put the raw materials weighed according to the mass percentage into a stirring device for mixing and stirring, and add the auxiliary materials, binders and additives weighed according to the mass percentage and an appropriate amount of water into the stirring device in sequence during the stirring process. At the same time, control the stirring time and stirring speed of the stirring device to adjust the fluidity and plasticity of the casting material, and obtain a corundum high-strength and wear-resistant casting material.

8. The corundum high-strength wear-resistant casting material according to claim 7, characterized in that: The stirring time of the stirring device is set between fifteen minutes and twenty minutes, and the stirring speed of the stirring device is set between three thousand revolutions per minute and five thousand revolutions per minute.

Citation Information

Cited By

  • Al2O3-SiO2 refractory brick for hazardous waste incinerator and preparation method of Al2O3-SiO2 refractory brick

    CN120647402A

  • Polycrystalline alumina fiber-based refractory material and preparation method thereof

    CN120717775A